2019
DOI: 10.3390/s20010072
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Acoustic Wave Platform Deployment in the Amazon River: Impact of the Water Sample on the Love Wave Sensor Response

Abstract: This paper presents an experimental platform allowing in situ measurement in an aqueous medium using an acoustic Love wave sensor. The aim of this platform, which includes the sensor, a test cell for electrical connections, a microfluidic chip, and a readout electronic circuit, is to realize a first estimation of water quality without transportation of water samples from the field to the laboratory as a medium-term objective. In the first step, to validate the ability of such a platform to operate in the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Moreover, underwater acoustic measurement commonly reveals an additional attenuation of the acoustic wave in the order of −10 dB of losses [ 21 ]. In our case, and surprisingly, a good recovery of the “dB” responses with adjacent water can be observed ( Figure 13 ), suggesting that EPS acts as a guiding layer for the acoustic wave, allowing enhanced propagation with water as a detection medium contrarily to air.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, underwater acoustic measurement commonly reveals an additional attenuation of the acoustic wave in the order of −10 dB of losses [ 21 ]. In our case, and surprisingly, a good recovery of the “dB” responses with adjacent water can be observed ( Figure 13 ), suggesting that EPS acts as a guiding layer for the acoustic wave, allowing enhanced propagation with water as a detection medium contrarily to air.…”
Section: Resultsmentioning
confidence: 99%
“…That could be related mainly to the higher molecular weight of mercury when compared with cadmium. It was indeed shown that the adsorbed mass affects the response of the acoustic Love wave sensing and, hence, improves sensitivity [ 21 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simpler and cheaper analytical methods are needed and, in this sense, biosensors have received great attention [ 27 29 ]. Biosensors belong to a category of analytical devices capable of providing a measurable output signal using the recognition of a substance of interest via a biological recognition unit.…”
Section: Introductionmentioning
confidence: 99%
“…Tigli et al developed a surface acoustic wave (SAW) device using a gold layer to immobilize specific antibodies on its surface in order to detect a specific antigen that is a cancer biomarker [14]. Another application of mass sensing devices is to determine water quality by measuring and characterizing pH; biochemical oxygen demand; total organic carbon; and nitrate, nitrite, ammonia, chlorine, and fluoride concentrations [15,16]. Tamarind et al presented a surface acoustic wave microfluidic chip with the ability to assess water quality on-site [15].…”
Section: Introductionmentioning
confidence: 99%